Sistem Pelacakan Lokasi Petugas Survei RTLH Menggunakan GPS Android dan WebGIS - Khairil Hamdi; Budi Sunaryo; Arianto Arianto; Yuhefizar; Imam Gunawan (Ikatan Ahli Informatika Indonesia (IAII), 2019)
The feasibility of a home for family residence is the basis for growing and developing a better family life. The roof, floor, and walls are data on the indicator of the feasibility of the house at the time of the survey. The need for a system that can display RTLH locations in the Web Geographic Information System (WebGIS) accompanied by detailed RTLH data and photos. This study explains how the system tracks the location of RTLH survey data officers using Android GPS, then represents it on WebGIS. The tracking method starts when the clerk fills out the home data input form via the Android application. Location coordinates in the form of latitude and longitude will be detected automatically and become input parameters accompanied by photos and RTLH data details. Offline data will be stored in SQLite then sent to MySQL via database synchronization while online. The purpose of this research is to establish a location tracking system for RTLH survey officers to facilitate the validation process of data suitability between data and facts in the field. This system managed to track the location of RTLH survey officers by being marked by the appearance of markers on the Google Map on the WebGIS application. From a total of 14,949 houses in Kota Solok in December 2018, there were 938 RTLH. From 938 RTLH, the coordinates of the location of latitude and longitude are 100%.